Maternal and fetal predictors of anthropometry in the first year of life in offspring of women with GDM - Antoniou, Maria-Christina; Quansah, Dan Yedu; Mühlberg, Suzanne; Gilbert, Leah; Arhab, Amar; Schenk, Sybille; Lacroix, Alain; Stuijfzand, Bobby; Horsch, Antje; Puder, Jardena Jacqueline (Frontiers in Endocrinology, 2023)
Introduction Gestational Diabetes Mellitus (GDM) carries an increased risk for adverse perinatal and longer-term cardiometabolic consequences in offspring. This study evaluated the utility of maternal anthropometric, metabolic and fetal (cord blood) parameters to predict offspring anthropometry up to 1 year in pregnancies with GDM. Materials and Methods In this prospective analysis of the MySweetheart study, we included 193/211 women with GDM that were followed up to one year postpartum. Maternal predictors included anthropometric (pre-pregnancy BMI, gestational weight gain (GWG), weight and fat mass at the 1st GDM visit), and metabolic parameters (fasting insulin and glucose, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), Quantitative insulin-sensitivity check index (QUICKI), HbA1c, triglycerides, and high-density lipoprotein (HDL) at the 1st visit and HbA1c at the end of pregnancy). Fetal predictors (N=46) comprised cord blood glucose and insulin, C-Peptide, HOMA-IR, triglycerides and HDL. Offspring outcomes were anthropometry at birth (weight/weight z-score, BMI, small and large for gestational age (SGA,LGA)), 6-8 weeks and 1 year (weight z-score, BMI/BMI z-score, and the sum of 4 skinfolds). Results In multivariate analyses, birth anthropometry (weight, weight z-score, BMI and/or LGA), was positively associated with cord blood HDL and HbA1c at the 1st GDM visit, and negatively with maternal QUICKI and HDL at the 1st GDM visit (all p ≤ 0.045). At 6-8 weeks, offspring BMI was positively associated with GWG and cord blood insulin, whereas the sum of skinfolds was negatively associated with HDL at the 1st GDM visit (all p ≤0.023). At 1 year, weight z-score, BMI, BMI z-score, and/or the sum of skinfolds were positively associated with pre-pregnancy BMI, maternal weight, and fat mass at the 1st GDM visit and 3rd trimester HbA1c (all p ≤ 0.043). BMI z-score and/or the sum of skinfolds were negatively associated with cord blood C-peptide, insulin and HOMA-IR (all p ≤0.041). Discussion Maternal anthropometric, metabolic, and fetal metabolic parameters independently affected offspring anthropometry during the 1st year of life in an age-dependent manner. These results show the complexity of pathophysiological mechanism for the developing offspring and could represent a base for future personalized follow-up of women with GDM and their offspring.